Pahljačniki (Coleoptera: Scarabaeidae) kot gospodarsko pomembni škodljivci in možnosti njihovega zatiranja z entomopatogenimi glivami - Praprotnik, Eva (Acta agriculturae Slovenica, 2022)
Scarab beetles (Coleoptera: Scarabaeidae) are a cosmopolitan group of beetles found on all continents except Antarctica. Because of their size, vibrant colors, and above all their role in the ecosystem, they are one of the most recognizable and studied taxons of beetles. Most larvae and adult beetles of species belonging to subfamilies Melolonthinae, Rutelinae, Dynastinae and Cetoniinae feed on plant organs such as roots, leaves, flowers and young fruits and are thus considered to be species of economic importance. In this article we describe some of the most economically important species of scarabs, including their most common host plants. Because the use of chemical insecticides to control scarabs is often limited, the implementation of entomopathogenic fungi as biological control agents is an appropriate alternative based on the rational use of microorganisms to maintain an environmentally balanced level of the pest population. Representatives of the genera Beauveria and Metarhizium are the most commonly used entomopathogenic fungi to control larvae (white grubs) of scarab beetles. Biological control by entomopathogenic fungi has shown to be effective in some cases, however host range is often speciesspecific. Therefore, in order to effectively use the entomopathogens against scarab beetles, one needs to identify target species in grub-infested area and consequently select strains that are capable of overcoming the host’s defences.
Keywords: biological control; biotično zatiranje; entomopathogenic fungi; entomopatogene glive; ogrci; pahljačniki; scarab beetles; Scarabaeidae; white grubs